Economics of technological change and the natural environment: How effective are innovations as a remedy for resource scarcity? - Lucas Bretschger (ETH Zurich, CER-ETH - Center of Economic Research, 2004)
The paper aims to substantiate the importance of endogenous innovations when evaluating the compatibility of natural resource use and economic development. It explains that technological change has the potential to compensate for natural resource scarcity, diminishing returns to capital, poor input substitution, and material balance restrictions, but is limited by various restrictions like fading returns to innovative investments and rising research costs. It also shows how innovative activities are fostered by accurate price signals and research-favouring sectoral change. The simultaneous effects of increasing technical knowledge, decreasing resource inputs, and increasing world population largely determine the chances of long-run sustainable development. Consequently, future research has to be directed at a more thorough understanding of the mechanisms driving innovations in the presence of natural resource scarcity.
Keywords: Q20; Q30; O41; O33; 330; endogenous technological change; environment; natural resources; sustainability; Endogenes Wachstumsmodell; Nachhaltige Entwicklung; Ressourcenökonomik